Peningkatan Kesadaran dan Perilaku Hidup Bersih melalui Edukasi dan Pendampingan Pengolahan Sampah Rumah Tangga di Desa Kalanganyar - Masykhun, Ahmad Fulkil (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2026)
The problem of household waste in Kalanganyar Village, Sedati District, Sidoarjo Regency, is increasing along with population growth, while residents' knowledge about waste sorting is still minimal and processing facilities are limited. This community service program aims to increase awareness and cleanliving behavior through education and mentoring on household waste processing based on the 3R concept (Reduce, Reuse, Recycle). This activity adopts an Asset-Based Community Development (ABCD) approach that focuses on mapping and utilizing local potential, such as health cadres, youth organizations, the spirit of mutual cooperation, and the availability of potential land. The implementation methods include appreciative inquiry, focus group discussions (FGDs), in-depth interviews with the Head of the Sopo Nyongko TPS and community leaders, participatory observation, and practical mentoring for housewives, youth organizations, and TPS managers on February 9. The results of the activity showed an increase in residents' understanding of PHBS and waste management, indicated by the enthusiasm of participants during the educational session. The program also successfully activated local agents of change: youth groups began implementing inorganic waste recycling, and health cadres designed a home-based waste sorting system.